Atlas of the Messier objects highlights of the deep sky - Stoyan, Ronald 1972-; Schröder, Klaus-Peter (Cambridge University Press, 2024)
Messier's catalog of 110 star clusters, nebulae, and galaxies is the most popular list of deep sky gems. The first edition of this stunning reference atlas was hailed as the most comprehensive, detailed, and beautiful account of the Messier objects then available. The second edition continues this trend, with thoroughly investigated and updated astrophysical, historical, and observational information for every object. The main object photos have all been replaced with more than 150 new images from some of the world's best amateurs displaying the objects' splendor through large-scale color images. Historical sketches from classical observers from the nineteenth century are presented, alongside the author's modern deep-sky drawings. Extensive information is given on visual observation from using the naked eye and binoculars through to large modern amateur telescopes. Astronomers of all abilities will delight in the Atlas's return as your guide to the sky's finest objects